The conceptual framework of housing purchase decision-making process - Hassan, Mohammad Mujaheed; Ahmad, Nobaya; Hashim, Ahmad Hariza (Human Resource Management Academic Research Society, 2021)
Buying a housing property is exciting because it marks the beginning of a whole new chapter. Before start looking for a house, it is very important to understand the intention of buying a housing property, whether it is as an investment or for self-occupation. This will affect the type of property to be purchased, whether it is a landed property or a high-rise building. Many potential homebuyers, especially first-time homebuyers, make buying mistakes for the wrong reasons, which makes the process of trying to sell their homes long and expensive. Deciding on the type of property is one thing, but then you must weigh all the pros and cons, as well as the average house price, which can vary greatly. Housing property is a commodity and involves multiple processes. Therefore, this article intends to study and develop the conceptual framework of the housing purchase decision-making process. This article first reviews the conceptual definition of housing purchase intentions and decisions. Next, this article reviews past research to understand the similarities of housing purchase intentions, preferences, and decision-making, and to develop a basic conceptual framework. This article also discusses consumer behaviour as homebuyers in the housing purchase decision-making process.